DEVELOPMENT OF AUTONOMOUS MODULAR AQUAPONIC SYSTEM - KHALID, MUHAMMAD HADIF AIMAN (2018)
The aquaponics systems focused on increasing economically and sustainability of indoor and outdoor fish farming. Aspect like sustainability, development and economically efficiency improve of farmer health we must reconsider the agriculture sciences, by this we understand that we must develops technologies friendly for the environment. Combining aquaculture with hydroponics we obtain a new innovation named aquaponics which respects principles of sustainable agriculture (wastewater bio filtration by plants) and gives us the possibility to increase economic efficiency with an additional production (organic vegetables) to produce the nutrient rich food. The efficiency of the aquaponics garden was depending on the farmer which is, the reaction of the farmer will affect directly towards its garden which is the fish lack of food, or the water gets too acidic. Thus, the effective way to overcome the problem is by making an autonomous system for the aquaponic to make it more effective and have fast reaction needed for the plant and fish.